Isochlorogenic Acid A Attenuates the Progression of Liver Fibrosis Through Regulating HMGB1/TLR4/NF-κB Signaling Pathway - Xin Liu; Xin Liu; Kai Huang; Ru Jiao Zhang; Dan Mei; Bo Zhang (Frontiers Media S.A., 2020)
Liver fibrosis, a chronic damage process related to further progression of hepatic cirrhosis, has yet no truly effective treatment. Isochlorogenic acid A (ICQA), isolated from a traditional Chinese herbal medicine named Laggera alata (DC.) Sch.Bip. ex Oliv. (Asteraceae), is proved to exhibit anti-inflammatory, hepatoprotective and antiviral properties. However, the actions of ICQA on liver fibrosis are poorly understood. The purpose of this study was to evaluate the actions of ICQA on liver fibrosis and clarify the underlying mechanism. It was found that ICQA had significant protective actions on liver injury, inflammation as we as fibrosis in rats. Meanwhile, ICQA prevented hepatic stellate cells (HSC) activation, indicated by its inhibitory effect on the overexpression of α-smooth muscle actin (α-SMA). In addition, the reduced fibrosis was found to be associated with the decreased protein expression of high-mobility group box 1 (HMGB1) as well as toll like receptor (TLR) 4. Simultaneously, ICQA can suppress the cytoplasmic translocation of HMGB1 in rat liver. Further investigations indicated that ICQA treatment dramatically attenuated the nuclear translocation of the nuclear factor-kB (NF-κB) p65 and suppressed the hepatic expression of p−IκBα in rats with liver fibrosis. Taken together, our study indicated that ICQA could protect against CCl4-induced liver fibrosis probably through suppressing the HMGB1/TLR4/NF-κB signaling pathways.